Project to enrich Felda youths - New Straits Times, Punitha Kumar (2012)
SOME 1.6 million youths will benefit from the Felda New Generation Development· Model project between Universiti Putra Malaysia (UPM)and Felda. The Federal Land Development Authority (Felda) chairman Tan Sri Mohd Isa Abdul Samad said the nine-month project sought expertise from 17 UPM experts in various fields.